Hypertensive diseases of pregnancy predict parent-reported difficult temperament in infancy - Robinson, M.; Oddy, W.; Whitehouse, A.; Pennell, C.; Kendall, Garth; McLean, N.; Jacoby, P.; Zubrick, Stephen; Stanley, F.; Newnham, J. (Lippincott Williams & Wilkins, 2013)
Objective: Recent research has linked hypertensive diseases of pregnancy with adverse neurodevelopmentaloutcomes in childhood and adulthood. This study aimed to establish whether such effects areobserved in infancy. Methods: This was a prospective pregnancy cohort study of 2,785 pregnancies withcomplete data on hypertensive diseases of pregnancy. Mothers completed a validated Australian adaptationof the Toddler Temperament Scale when the children were 1 year of age (n 5 2,384). Algorithms were used toclassify children as difficult, slow to warm up, intermediate high, intermediate low, or easy, on the basis oftheir temperament scores. We then grouped difficult and intermediate-high infants together and comparedthem with easy, intermediate-low, and slow-to-warm-up infants. We used a multivariable logistic regressionmodel and adjusted for known biomedical, sociodemographic, and psychological factors from the pre- andpostnatal period that may influence child behavioral development. Results: After adjusting for confounders,mothers who were diagnosed with gestational hypertension (odds ratio [OR], 1.36; 95% confidence interval[CI], 1.06–1.75) or preeclampsia (OR, 2.23; 95% CI, 1.18–4.23) were more likely to report that their infantswere in the difficult or intermediate-high classifications in the first year of life compared with infants born tomothers without gestational hypertension or preeclampsia. Conclusion: These data suggest that the linkbetween maternal hypertensive diseases of pregnancy and child behavioral development begins in the firstyear of life.